RELIGIOUS MODERATION IN THE INTERPRETATION OF THE QUR'AN AND ITS RELEVANCE TO ISLAMIC RELIGIOUS EDUCATION IN INDONESIA - Mutaqin, Enjen Zaenal (TAWASUT, 2024)
This article discusses the concept of religious moderation in Tafsir of the Qur'an and its relevance to Islamic Religious Education in Indonesia. The background to this research is the importance of understanding moderation in the context of diversity in Indonesia, especially in Islamic religious education. The aim of this research is to analyze the concept of religious moderation contained in the book Mafātih al-Ghaib by Fakhruddīn al-Rāzi and the interpretation of the Indonesian Ministry of Religion, and relate it to the Islamic Religious Education curriculum in Indonesia. The research methodology used is a qualitative method with content analysis techniques. Primary data was obtained from moderation verses in the book Mafātih al-Ghaib and the tafsir of the Indonesian Ministry of Religion, while secondary data came from scientific journals, books and relevant previous research. The analysis was carried out using a thematic and comparative approach, and using Yusuf al-Qaradawi's moderation theory. The research results show that the concept of religious moderation in Tafsir of the Qur'an can be applied relevantly in the context of Islamic Religious Education in Indonesia. These findings provide an original contribution to the understanding of religious moderation and can guide the development of inclusive and moderate religious curricula.